Altruism as a scaling ingredient: an exploration of the adoption of the Laboy tiller in Aurora - Manalo, Jaime A.; Orcullo, Louie Gerard F.; de Leon, Teresa Joi P. (Frontiers in Sustainable Food Systems, 2025)
The Laboy tiller was developed to address the challenges of preparing fields with laboy soil conditions. This study uses the scaling ingredients framework developed by PPPlab and CIMMYT to examine how the machine scaled from its initial project in San Luis, Aurora, Philippines. In-depth interviews with farmers (n = 28) and key informants (n = 12) were conducted to address the research questions. The results show a lack of concerted efforts in addressing some of the scaling ingredients, such as collaboration, evidence and learning, leadership and management, and public sector governance. Consequently, the Laboy tiller experienced limited scaling outside of San Luis town. However, it had a profound impact on the farmers of laboy areas in Aurora, where the concept of altruism emerged as a critical scaling ingredient. Altruism facilitated the Laboy tiller’s dissemination through the personal networks of its initial owners, who valued and maintained the machine over time. Recognizing altruism as a key scaling ingredient could enhance the scaling efforts of other innovations by encouraging beneficiaries to actively participate in the continued uptake and sustainability of introduced innovation.